A Microarray-based Multiplexed Scanometric Immunoassay for Protein Cancer Markers Using Gold Nanoparticle Probes - Kim, Dongwoo (2009)
We report the use of electroless gold deposition as a light scattering signal enhancer in a multiplexed, microarray-based scanometric immunoassay using gold nanoparticle probes. The use of gold development results in greater signal enhancement than the typical silver development, and multiple rounds of metal development were found to increase the resulting signal compared to one development. Using these conditions, the assay was capable of detecting 300 aM (~ 9000 copies) of prostate specific antigen in buffer and 3 fM in 10% serum. Additionally, the highly selective detection of 3 protein cancer markers at low pM concentrations in buffer and 10% serum was demonstrated. The use of gold deposition may have significant utility in scanometric detection schemes and broader clinical and research applications.